Enhancement of Surface Roughness and Growth Morphology of Nanoporous Anodic Alumina from Commercially Aluminum Alloy 1050 Using Two-Step Electrochemical Polishing. Issue 10 (1st January 2018) - Chung, C. K.; Tsai, C. H.; Wang, Z. W.
Abstract : This article investigates the two-step electrochemical polishing process for improving growth of nanoporous anodic aluminum oxide (AAO) from commercially low-purity (<99.5%) aluminum alloy 1050 (AA1050) at room temperature (25°C). The conventional one-step electropolishing is a vital pretreatment process before the anodic oxidation for reducing the surface roughness of high-purity (>99.99%) aluminum to promote the AAO pore structure anodized at low temperature (0∼10°C). The AAO pore quality is related to the surface roughness and purity of aluminum, especially the commercial aluminum alloy is much rougher than high-purity aluminum. Moreover, the high-purity aluminum is rather expensive and of low strength for practical application. Here, we propose a novel two-step electropolishing approach to improve the anodization of low-cost commercial AA1050 alloy with low purity and high roughness. The optimum electrolyte ratio and polishing time of the two-step electropolishing can effectively achieve the smooth surface for promoting AAO growth. The pore size distribution and deviation of AAO from AA1050 at 25°C are enhanced from 17.1 ± 4.90 nm with 15.62% max distribution (one-step electropolishing) to 23.5 ± 3.74 nm with 19.35% max distribution (two-step electropolishing) at stable time-dependent current evolution.